The Association Between Sarcopenic Obesity and Hypertension, Diabetes, and Abnormal Lipid Metabolism in Chinese Adults - Yin T (Dove Medical Press, 2021)
Ting Yin,1,2,* Jia-Xing Zhang,1,* Fa-Xuan Wang,1,2 Jian-Hua Zhao,3 Yu Zhao,1,2 Lan Liu,1,2 Xiu-Ying Liu,1,2 Yu-Hong Zhang,1,2 Yi Zhao1,2 1School of Public Health and Management, Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 2Key Laboratory of Environmental Factors and Chronic Disease Control, Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 3Ningxia Center for Disease Control and Prevention, Yinchuan, Ningxia, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu-Hong Zhang; Yi ZhaoDepartment of Epidemiology and Health Statistics, School of Public Health and Management, Ningxia Medical University, 1160, South Shengli Street, Yinchuan, Ningxia Hui Autonomous Region, People’s Republic of ChinaTel +86 0951-6980144Fax +86 0951-6980144Email zhabour@163.com; zhaoyi751114@hotmail.comObjective: Sarcopenic obesity is associated with several negative health outcomes. However, there are only a few studies on the relationship between SO and metabolic diseases such as diabetes, hypertension, and abnormal lipid metabolism in Chinese adults. The aim of this work was to evaluate the association between SO and hypertension, diabetes, and abnormal lipid metabolism in Chinese adults, and explore the prediction of SO using relevant anthropometric indicators.Materials and Methods: All participants underwent a questionnaire interview for the collection of demographic data. Thereafter, they underwent physical examination for the measurement of anthropometric variables, which was performed using bioelectrical impedance analysis. Biochemical measurements were determined according to standard laboratory procedures used for the evaluation of blood parameters.Results: We included 14,926 patients aged 35– 74 years old. The mean age of the participants was 56.75 ± 9.76 years old, and 39.80% of them were male. The mean body mass index (BMI) was 24.94 ± 3.40 kg/m2, and the overall prevalence of SO was 65.1%. The results showed that shorter people; people with faster heart rate; heavier weight; lower waist circumference (WC), BMI, triglyceride level, total cholesterol, and low-density lipoprotein cholesterol levels; and higher high-density lipoprotein cholesterol level are at risk for SO.Conclusion: The prevalence of SO is high (65.1%) in Chinese adults aged 35– 74 years old. The occurrence of SO is related to hypertension, diabetes, and abnormal lipid metabolism. BMI, WC, and waist-hip ratio may be predictive indicators of SO. The incidence of SO may be reduced by timely intervention and health education for persons at risk of the condition.Keywords: sarcopenic obesity, hypertension, diabetes mellitus, abnormal lipid metabolism